Suicidal Behaviour of the Population in Poland as an Element of Risk in Life Insurance - Wieteska, Stanisław (Studia Oeconomica Posnaniensia, 2026)
For many years in Poland the phenomenon of suicide amongst the population has been observed. Life insurance companiesare required to pay benefits due to a death from suicide from two years after the signing of the life insurance contract. In this paper we present concepts related to suicide as well as a statistical analysis of this phenomenon. Against this background we indicate the causes and effects of suicidal behaviour. In the final part of the article we make a thorough analysis of high-risk social groups. Through the use of tests and scales we can assess the risk of unexpected suicides and incorporate these in the calculation of the insurance premium.